Artlangs in computer games: taxonomy and functions - Artamonova, Mariia Valerievna; Mironchenko, Roman Sergeevich; Tulina, Ekaterina Valer'evna (Litera, 2024)
This article is devoted to the study and analysis of artificial languages, namely artlangs, which are used to create a unique setting and functionality in computer game discourse (using the example of the computer game “Chants of Sennaar”). The object of the study is arlangs in computer game discourse. The subject of the study is the functional features and roles of artlangs in computer game discourse, their world-forming and plot-forming functions. To analyze the classification and functions of artlang in the virtual space of a computer game, the authors of the article use an integrated approach (integrative, exploratory and configurative) in order to identify lexical, grammatical and syntactic features of artlangs, as well as take into account their connection with game mechanics, in-game space and the communicative reality of computer games. Linguistic analysis in the article is based on a comparison of 5 artificial languages specially created for the game in question, each of which has its own unique functionality and structure that reflect the specifics of the group of characters that use it. The scientific novelty of the work lies in the fact that the authors of the study tried to deduce the universal and specific characteristics of artificial languages (artlangs) in computer game discourse. The authors conclude that computer-gaming discourse offers a fundamentally new, different from fiction, interactive space for the creation and functioning of artificial languages, as well as for conducting unique linguistic experiments at the intersection of grammar, morphology and semantics. In addition, the authors concluded that the implementation of these artlangs within the framework of all three approaches (integrative, exploratory and configurative) allows fictional languages (artlangs) to fully function and develop as independent linguistic systems, enriching the gaming experience and constructing a new communicative reality.